Visual Branding : Pemanfaatan FIGMA dalam Perancangan Logo HIMA Akuntansi Universitas Nahdlatul Ulama Kalimantan Timur (Yayasan Kawanad, 2022)
Visual branding is an effort to presented and introduced a work (design) to the public or the market. There are many things that must be prepared, including how to process ideas into works. The use of Figma is an option in visualizing the Logo from HIMA Accounting UNU East Kalimantan, besides Figma being online-based and having Cloud Storage, Figma also provides results that are able to compete with other editing applications that require quite high laptop/pc specifications. The convenience provided by Figma makes designers more efficient in terms of time and results. The logo is processed using a practice-based method (Practice Based Research) which uses 3 stages of the creative process from Hawkins: 1) Exploration Stage, 2) Improvisation Stage, 3) Manifestation Stage. The visual branding that is carried out is expected to be able to provide a positive response from the campus community and activities around it later, but it still requires additional introduction efforts in the form of optimizing social media and websites.